Operationalising communication rights: the case of a “digital welfare state” - Marko Ala-Fossi; Anette Alén-Savikko; Jockum Hilden; Minna Aslama Horowitz; Johanna Jääsaari; Kari Karppinen; Katja Lehtisaari; Hannu Nieminen (Internet Policy Review)
Academic debates tend focus on attempts to codify and promote communication rights at the global level. This article provides a model to analyse communication rights at a national level by operationalising four rights: access, availability, dialogical rights, and privacy. It highlights specific cases of digitalisation in Finland, a country with an impressive record as a promoter of internet access and digitalised public services. The article shows how national policy decisions may support economic goals rather than communication rights, and how measures to realise rights by digital means may not always translate into desired outcomes, such as inclusive participation in decision-making.